Per-oral endoscopic salpingo-oophorectomy (POESY) in humans: a prospective clinical feasibility study - Hornemann, Amadeus; Sütterlin, Marc; Kähler, Georg (Archives of gynecology and obstetrics, 2018)
Background and aims: Natural orifice translumenal endoscopic surgery (NOTES) procedure describes a surgical approach using natural orifices. We describe a prospective non-comparative clinical study on transgastric salpingo-oophorectomy in humans. Methods: Patients with indication for salpingo-oophorectomy were offered the transgastric approach. This paper presents the data of the first 6 patients, in whom the procedure was performed. After gastroscopic incision in the anterior corpus wall we advanced the flexible gastroscope into the abdominal cavity. With the help of a transvaginally introduced 10 mm trocar and, if the uterus was present, an intrauterine manipulator, the salpingo-oophorectomy was performed. The colpotomy was dilated and the specimens were extracted in a bag. The gastrotomy was closed with an over-the-scope-clip and the colpotomy with a running suture. Results: The planned salpingo-oophorectomy was performed successfully in all patients. All patients recovered quickly and were discharged between the third and fifth day. In one patient a gastric bleeding was seen on the first postoperative day. The bleeding was clipped gastroscopically, all other follow ups were uneventful. Conclusion: Our study demonstrates the feasibility of the transgastric access to the pelvis. The gastroscope provided excellent optical control and good tissue preparation. Therefore, we conclude that pure NOTES procedures using the transgastric access to the adnexa are feasible. An increasing role of transgastric procedures for diseases in the pelvic region can be expected in particular if new endoscopic platforms with better means of instrumentation and tissue management become available.